Effects of Pre-questioning on the Students’ Reading Comprehension - Abdullah Syukur (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2022)
This study was conducted to investigate the effect of Pre-questioning on the Students’ Reading Comprehension of the fifth semester students of Informatic Study Program Faculty of Computer Engineering Cokroaminoto Palopo University in academic year 2022/2023. The forms of questions were in multiple choice and essay, multiple choice used for reading comprehension tests and essay used for Pre-questioning tests. There were 40 students of the fifth semester students of Informatic Study Program Faculty of Computer Engineering Cokroaminoto Palopo University in academic year 2022/2023 as the sample on this study. The researcher used pre experimental method in this study. the sample was taken by using random sampling technique. There are two kinds of instrument used in this research, namely test and questionnaire. The result of the research shows that the reading comprehension ability of the fifth semester students of Informatics Study Program Faculty of Computer Engineering Cokroaminoto Palopo University was very effective. It was proven by the mean score in post-test was 7.55 and the T-test value 43.375 which was higher than the T-table value 2.315. And the students were interested in learning reading comprehension using pre-questioning technique.